Lactic acid production by Lactobacillus casei using a sequence of seasonally available fruit wastes as sustainable carbon sources - Costa, Stefania; Summa, Daniela; Radice, Matteo; Vertuani, Silvia; Manfredini, Stefano; Tamburini, Elena (Frontiers in Bioengineering and Biotechnology, 2024)
Lactic acid (LA) production from fossil resources is declared to be unsustainable due to their depletion and environmental concerns. Thus, this study aimed at optimizing the production of LA by Lactobacillus casei in a cultured medium containing fruit wastes (FW) from agro-industries and second cheese whey (SCW) from dairy productions, supplemented with maize steep liquor (MSL, 10% v/v) as nitrogen source. FW have been selected based on seasonal availability: early summer (early ripening peach), full summer (melon), late summer (pear) and early autumn (apple), and SCW as annual waste. Small-scale preliminary tests, as well as controlled fermenter experiments, have shown that the potential for using various food wastes (FW) as substrates for lactic acid (LA) fermentation is promising, except for apple pomace. A 5-cycle repeated batch fermentation was conducted to optimize waste utilization and LA production, resulting in a total of 180.56 g/L of LA with a volumetric productivity of 0.88 g/L•h. Subsequently, mechanical filtration and enzymatic hydrolysis were attempted. The total amount of LA produced in the 5-cycle repeated batch process was 397.1 g/L over 288 hours, achieving a volumetric productivity of 1.32 g/L•h. These findings suggest a promising biorefinery process for low-costs LA production from agri-food waste.